2019
DOI: 10.1093/nar/gkz659
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a caged lentiviral vector through an unnatural amino acid for photo-switchable transduction

Abstract: Application of viral vectors in gene delivery is attracting widespread attention but is hampered by the absence of control over transduction, which may lead to non-selective transduction with adverse side effects. To overcome some of these limitations, we proposed an unnatural amino acid aided caging–uncaging strategy for controlling the transduction capability of a viral vector. In this proof-of-principle study, we first expanded the genetic code of the lentiviral vector to incorporate an azido-containing unn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…89,90 Further, genetically modified viruses can enhance TE, 91,92 broaden the tropism, 63,93 enable fluorescent imaging, 85 escape neutralizing antibodies, 94,95 generate stimuli responsive vectors, 96 e.g. by light 97,98 or enzymes, 99 and target cells. 100,101 Comprehensive recent reviews on bioengineering AAV can be found elsewhere.…”
Section: Physical Methodsmentioning
confidence: 99%
“…89,90 Further, genetically modified viruses can enhance TE, 91,92 broaden the tropism, 63,93 enable fluorescent imaging, 85 escape neutralizing antibodies, 94,95 generate stimuli responsive vectors, 96 e.g. by light 97,98 or enzymes, 99 and target cells. 100,101 Comprehensive recent reviews on bioengineering AAV can be found elsewhere.…”
Section: Physical Methodsmentioning
confidence: 99%
“… 324 , 325 Such lentiviral vectors are being continuously developed and optimized, and could enjoy a broader application in future gene therapies. In addition, the development of safer vectors via photo-switchable non-canonical amino acids to regulate transgene expression in a spatial and temporal manner, 326 also represent the next generation of lentiviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…To externally control transgene delivery, light is the optimal stimulus as it can be easily applied with high spatiotemporal precision in a reversible manner. As existing technologies for light‐controlled viral gene delivery were hampered by the need for cytotoxic ultraviolet (UV) light (Goater et al., 2000; Ito et al., 2004; Pandori & Sano, 2000; Pandori et al., 2002; Ulrich‐Vinther et al., 2002; Wang et al., 2019), the required uptake of viral vectors to both target and off‐target cells before optical control (Bonsted et al., 2006; Bonsted, Hogset, Hoover, & Berg, 2005; Goater et al., 2000; Gomez, Gerhardt, Judd, Tabor, & Suh, 2016; Hagihara et al., 2020; Hogset et al., 2002; Ito et al., 2004; Tahara et al., 2019; Ulrich‐Vinther et al., 2002; Wang et al., 2019), or the requirement for genetic pre‐engineering of the target cells to express the photoreceptor (Gomez et al., 2016), we recently published the OptoAAV technology that overcomes these limitations (Hörner et al., 2021). The OptoAAV system allows the spatially resolved delivery of transgenes into native target cells upon illumination with low‐intensity red light and is discussed in more detail in the section Background Information.…”
Section: Introductionmentioning
confidence: 99%